METTL16-dependent GPX4 m6A modification links ferroptosis to NSCLC TKIs resistance - Yingou Zeng; Qiang Wang; Di Qiao; Bin Dai; Yunlong Wu; Meng Wang; Zhe Fan; Jia Chen (BMC Cancer)
Abstract Background Non-small-cell lung cancer (NSCLC) is a highly aggressive cancer with a poor prognosis, largely due to increasing resistance to Tyrosine Kinase Inhibitors (TKIs). The mechanisms of NSCLC TKI resistance remain unknown. This study aimed to elucidate the molecular mechanism of METTL16-mediated GPX4 m6A modification and its underlying function in regulating the proliferation and AZD-9291 resistance of NSCLC. Methods TCGA, and GEO datasets were used to analyze the differential expression of m6A-modified GPX4 in NSCLC and adjacent tissues, and its impact on prognosis. Then the GPX4 induced ferroptosis escape promoted the proliferation and AZD-9291 resistance of PC9 and HCC827 cells. The regulatory mechanism of METTL16/GPX4 and its interaction in cancer progression were investigated through MeRIP, Western blots, dual-luciferase reporter assay, and rescue experiments. Results METTL16 was significantly upregulated in NSCLC tissue and was associated with a worse prognosis. Overexpression of METTL16 significantly promoted the proliferation and AZD-9291 resistance of NSCLC, while METTL16 knockdown inhibited the above phenotype. Through bioinformatic analysis and experimental results, we found that GPX4 mRNA is a substrate of METTL16. GPX4 was upregulated in AZD-9291-resistant NSCLC cells and ferroptosis was inhibited. As a key regulator of ferroptosis, METTL16 mediated GPX4 m6A modification promoted NSCLC proliferation and AZD-9291 resistance through inhibiting ferroptosis. Further, targeting METTL16 exhibited pro-ferroptosis function and AZD-9291 sensitivity of NSCLC. Conclusions In summary, we found that METTL16-mediated GPX4 modification promoted the proliferation and AZD-9291 resistance of NSLCL by inhibiting ferroptosis activity. Our study is expected to provide a novel insight and potential therapeutic target for NSCLC AZD-9291 resistance.